Present-day Crustal Deformation in West Sumatra After Series of Sumatran Great Earthquake from 2004-2010 - Satrio Muhammad Alif; Jenny Melynda Siagian; Ongky Anggara (Journal of Earth and Marine Technology (JEMT), 2023)
Present-day crustal deformation was an attempt to estimate earthquake potential, yet the presence of postseismic deformation should be carefully identified. Studying crustal deformation in West Sumatra has been important for this purpose since the series of Sumatran Great Earthquake from 2004-2010. This study utilized present-day GNSS data (2017-2021) and pre-2004 GNSS velocities to understand the present-day crustal deformation. Bernese 5.2 was used to process the GNSS data and linear regression was used to calculate present-day velocities. These velocities were transformed into an ITRF2000-based Sundaland plate reference frame and then the velocities were compared to pre-2004 velocities in the same reference frame. The present-day velocities were ranging from 28.4 mm/yr to 58.3 mm/yr in ITRF2014 and from 8.8 to 44.8 mm/yr in the Sundaland plate reference frame. This suggests West Sumatra was located on the Sumatra block of the Sundaland plate. The low velocity difference ( 11.7 mm/yr) with the random vector direction between present-day velocities and pre-2004 velocities shows that there is no postseismic deformation affecting West Sumatra. This proposes the utilization of present-day velocities for earthquake potential estimation in West Sumatra.